Conductance of L-shaped and T-shaped graphene nanoribbons. (February 2018) - Moysidis, Savvas; Karafyllidis, Ioannis G.
Abstract: Rectangular graphene nanoribbons with two contacts have been studied extensively as parts of several nanoelectronic devices. L-shaped and T-shaped graphene nanoribbons received a little or no attention until now. In this letter, we present computations of the conductance of L-shaped graphene nanoribbons with two contacts and of T-shaped graphene nanoribbons with tree contacts. We used tight-binding Hamiltonians and non-equilibrium Green's functions to compute their conductance. In L and T-shaped nanoribbons electrons are initially transported along a zigzag-edged nanoribbon, and then the direction of their motion changes by 90 O and are transported along an armchair-edged nanoribbon. Our results show that this change in direction of motion results in a zero-conductance region that extents about 0.25 eV below and above the Fermi level. This zero conductance region is large enough to cause current switching and, because of this, L and T-shaped graphene nanoribbons can be used as building blocks for logic gates.